The Changing Arctic Cryosphere and Likely Consequences: An Overview - M. S. Olsen; T. V. Callaghan; J. D. Reist; L. O. Reiersen; D. Dahl-Jensen; M. A. Granskog; B. Goodison; G. K. Hovelsrud; M. Johansson; R. Kallenborn; J. Key; A. Klepikov; et al. (AMBIO, 2011)
The Arctic cryosphere is a critically important component of the earth system, affecting the energy balance, atmospheric and ocean circulation, freshwater storage, sea level, the storage, and release of large quantities of greenhouse gases, economy, infrastructure, health, and indigenous and non-indigenous livelihoods, culture and identity. Currently, components of the Arctic cryosphere are subjected to dramatic change due to global warming. The need to document, understand, project, and respond to changes in the cryosphere and their consequences stimulated a comprehensive international assessment called “SWIPA”: Snow, Water, Ice, Permafrost in the Arctic. Some of the extensive key SWIPA chapters have been summarized and made more widely available to a global audience with multi-disciplinary interests in this Special Report of Ambio. In this article, an overview is provided of this Special Report in the context of the more detailed and wider scope of the SWIPA Report. Accelerated changes in major components of the Arctic cryosphere are documented. Evidence of feedback mechanisms between the cryosphere and other parts of the climate system are identified as contributing factors to enhanced Arctic warming while the growing importance of Arctic land-based ice as a contributor to global sealevel rise is quantified. Cryospheric changes will result in multifaceted and cascading effects for people within and beyond the Arctic presenting both challenges and opportunities.